The Relationship Between Training Methods, Competence, Employee Engagement, and Employee Performance - Wahyu Bagus Rilo; Anita Maharani (Kusuma Negara Business School, 2020)
This study aims to see the relationship between research methods, employee engagement, and employee performance. The phenomenon that appears in this research is that employee performance influence by training methods, the competencies possessed by employees, and the extent to which employees are involved in the organization. The research approach used is quantitative and processed using multiple regression. This study indicates that training methods and employee competencies affect employee performance due to employee engagement.